The Principle of Meaningful Participation in the Formation of the Maternity Leave Policies in Indonesia - Nur Rohanawati, Ayunita; Ardhany, Yustika (KnE Social Sciences, 2023)
The maternity leave policy in Indonesia is in the process of transitioning from a three month leave as per the Indonesian Employment Law to a six month leave in accordance with the Maternal and Child Welfare Bill (‘MCH Bill’). The government delayed the legalization of the bill due to the policy being controversial among the public, especially employers and workers. The controversy that occurred was a reaction to the exclusion of certain voices in the process of forming the MCH Bill. This research aimed to highlight the problem related to meaningful participation in the formation of maternity leave policy in Indonesia. The methodology used in this study is the legal doctrine method with a statutory and a conceptual approach. In the process of forming legislation in Indonesia, the principle of meaningful participation must be applied to accommodate the aspirations of all parties involved in the implementation of the law. In the context of the establishment of the MCH Bill, the meaningful participation of employers and workers is crucial because they are the main actors in the production process and the main actors in the MCH Bill. Keywords: Maternity Leave, Meaningful Participation, MCH Bill